2017
DOI: 10.1186/s40246-017-0126-2
|View full text |Cite
|
Sign up to set email alerts
|

Genomic variants in the FTO gene are associated with sporadic amyotrophic lateral sclerosis in Greek patients

Abstract: BackgroundAmyotrophic lateral sclerosis (ALS) is a devastating disease whose complex pathology has been associated with a strong genetic component in the context of both familial and sporadic disease. Herein, we adopted a next-generation sequencing approach to Greek patients suffering from sporadic ALS (together with their healthy counterparts) in order to explore further the genetic basis of sporadic ALS (sALS).ResultsWhole-genome sequencing analysis of Greek sALS patients revealed a positive association betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 48 publications
0
16
0
1
Order By: Relevance
“…[12][13][14][15] Further research elucidated more about the physiological role of FTO and revealed that FTO is not only associated with obesity but also with a seemingly unrelated disorder, neurodegeneration. [16][17][18][19][20][21] However, so far no direct link was provided regarding the mechanism for the effect of FTO on neuronal degeneration. In this study, we choose to study the effect of expressing the WT and the mutant FTO expressions on the soluble proteome of SH-SY5Y cells.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15] Further research elucidated more about the physiological role of FTO and revealed that FTO is not only associated with obesity but also with a seemingly unrelated disorder, neurodegeneration. [16][17][18][19][20][21] However, so far no direct link was provided regarding the mechanism for the effect of FTO on neuronal degeneration. In this study, we choose to study the effect of expressing the WT and the mutant FTO expressions on the soluble proteome of SH-SY5Y cells.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of m 6 A involvement in the pathogenesis of ALS is also emerging. In addition to its wide expression in brain, FTO has been shown to be highly expressed in lower motor neurons ( Mitropoulos et al, 2017 ). Whole-genome sequencing analysis of Greek patients with sporadic ALS revealed a positive association between FTO gene variants and the disease ( Mitropoulos et al, 2017 ).…”
Section: Rna M 6 a Methylation In Neurological Dismentioning
confidence: 99%
“…In addition to its wide expression in brain, FTO has been shown to be highly expressed in lower motor neurons ( Mitropoulos et al, 2017 ). Whole-genome sequencing analysis of Greek patients with sporadic ALS revealed a positive association between FTO gene variants and the disease ( Mitropoulos et al, 2017 ). Moreover, a targeted gene sequencing of RBPs in ALS patients identified rare deleterious polymorphisms at a significantly higher rate than control in the RBM15 gene and in its paralog RMB15B ( Cooper-Knock et al, 2017 ).…”
Section: Rna M 6 a Methylation In Neurological Dismentioning
confidence: 99%
“…In particular, the project aims to analyze (1) a large number of healthy donors of Hellenic origin, to determine the allelic architecture of the population, especially pharmacogenomic variants; (2) cohorts of patients suffering from rare multifactorial genetic diseases, such as amyotrophic lateral sclerosis, celiac disease, multiple sclerosis, etc., to identify their underlying genetic etiology; and (3) cohorts of patients suffering from monogenic diseases, such as cystic fibrosis and b-thalassemia, to identify genetic modifiers of the final clinical phenotype. So far, using this approach, a genomic locus was found to be associated with sporadic ALS in Greek patients via whole-genome sequencing 11 as well as a genomic locus associated with pediatric celiac disease in Greek patients. 12 Also, we have demonstrated the utility of whole-genome sequencing analysis in pharmacogenomics, using a Greek family as a paradigm.…”
Section: Key Componentsmentioning
confidence: 99%